Study of physico-geographical factors determining the tactical properties of terrain - Fedchenko, Oleksii (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The need for quantitative assessment of how physico-geographical conditions of terrain affect combat operations is driven by the transformation of the contemporary military environment. The increasing significance of maneuver and high-technology operations requires precise consideration of terrain factors in planning and conducting combat. Experience from recent armed conflicts, including the war in Ukraine, has shown that relief, forest cover, and road infrastructure substantially influence the effectiveness of unit employment, their mobility, concealment, and survivability. The development of geoinformation (GIS) technologies creates the conditions for building terrain-assessment models based on spatial data, digital relief models, and statistical analysis of natural components. Combined with military terrain-evaluation techniques, this enables the deployment of objective quantitative criteria for forecasting the suitability of areas for force deployment and maneuver. Accordingly, the relevance of this study lies in creating a scientifically grounded model that integrates the results of physico-geographical analysis into the system of military planning and command and control.M e t h o d s . The study employed general scientific methods: analysis, comparison, synthesis, systemic approach, and a structural-graphic method. Applying these methods made it possible to systematize the factors through which the physico-geographical environment affects military activity, to develop quantitative terrain-assessment criteria, and to construct a generalized structural-graphic model of the tactical terrain suitability for unit disposition.R e s u l t s . The study adapts a system of baseline evaluative indicators of the terrain′s physico-geographical factors (terrain dissection coefficient KTD, mean slope of the relief mr, degree of forest cover ml, and road-network density md) and integrates them into a unified index T for calculating the tactical requirements in support of unit military operations. The choice of indicators is justified by their tactical significance and the availability of source data; the formulas for computing each indicator are cited from published sources. An example is provided of the calculation and interpretation of terrain-suitability classes with respect to maneuverability, concealment, and logistical feasibility.C o n c l u s i o n s . The proposed and tested operationally oriented, generalized model for assessing tactical properties of terrain adapted to the requirements of planning and conducting combat in modern conflicts. The model integrates quantitative indicators of physico-geographical terrain factors, which are normalized and aggregated into a composite suitability index T using weighting methods. It enhances the accuracy of tactical terrain assessment, improves the effectiveness of unit employment, and can serve as a basis for preparing decisions on force disposition, engineering preparation of areas, and logistical support.
Keywords: physico-geographical conditions, relief, terrain mobility (passability), terrain assessment, road-network density, tactical terrain properties, combat employment of units